Mediated research encounters: methodological considerations in cross-language qualitative interviews. (December 2018) - Chiumento, Anna; Rahman, Atif; Machin, Laura; Frith, Lucy
Given increasing globalisation, the continuing prevalence of emergencies, and the importance of rigorous research to ensure the mental health needs of populations exposed to emergencies are effectively met, cross-language research will continue to arise. Drawing upon the lead author's experience of conducting a cross-language qualitative study in three post-conflict settings in South Asia, this article discusses methodological considerations raised when interviewing with interpreters. These include considering interpreter positionality and matching; the approach to cross-language mediation during interviews; and assessing the quality of interpreter facilitated interviews. Drawing upon approaches taken in this study, the important choices researchers face about how these are managed are examined, considering the roles of researcher and interpreter positionality, the research context, and the epistemological underpinnings of the research. The discussion further illuminates the interrelated methodological, practical and ethical considerations for other researchers embarking upon similar research.